Pengaruh Kualitas Layanan, Kualitas Produk, Promosi, dan Harga Normal terhadap Kepuasan dan Loyalitas Konsumen - Nathaza Gayatry Woen; Singgih Santoso (Jurnal Maksipreneur, 2021)
In many marketing activities, including fast-food, customer satisfaction is an important factor for the success of a business and has the possibility to influence customer loyalty in the future. The purpose of this study is to determine the effect of service quality, product quality, promotion, and fairness of prices on customer satisfaction and customer loyalty at Burger King outlets in Yogyakarta. The research will also use gender and education level as moderation variables. By using survey methods on 377 respondents and by testing the structural model using AMOS (Analysis of Moment Structure) software version 24, the results of the study show that service quality has a significant and positive effect on customer satisfaction, product quality has a significant and positive effect on customer satisfaction, promotion does not significantly influence customer satisfaction, fairness price has a significant and positive effect on customer satisfaction, and customer satisfaction has a significant and positive effect on customer loyalty. The results also show that gender and education levels moderate the relationship between variables in the research model.